Embracing the C preprocessor during refactoring. Issue 12 (26th June 2013) - Garrido, Alejandra; Johnson, Ralph
ABSTRACT C preprocessor directives are heavily used in C programs because they provide useful and even necessary additions to the C language. However, they are usually executed and discarded before any analysis is applied on C programs. In refactoring, preprocessor directives must be preserved through the whole process of parsing, analysis and transformation to retain editable yet correct source code. We propose a new preprocessing approach and special program representations that allow a program to be analyzed and transformed without losing its preprocessor directives, but treating them as first‐class program entities. These representations are essential for a correct refactoring tool. We also describe the challenges that preprocessor directives bring to refactoring and how the program representations that we propose solve those challenges. Finally, we give details of two refactorings and present some case studies with our successfully applied solution. Copyright © 2013 John Wiley & Sons, Ltd.